2013
DOI: 10.1177/1350650113500483
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of large thrust-bearing performance at transient states, warm and cold start-up

Abstract: The start-up of a large hydrodynamic thrust bearing of a vertical hydrogenerator is one of the most critical situations during the lifetime of a bearing. Hydrodynamic load capacity is low due to low speed and higher thermal deformations of the pad. A new approach to the simulation of a hydrodynamic bearing is shown in this article. A combination of finite elements method and computational fluid dynamics is used to perform the transient simulation of the bearing start-up. A bidirectional bearing of a pump-stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 8 publications
0
19
0
Order By: Relevance
“…It was assumed similarly as in Refs. [10,16] that recess has conical shape (truncated cone, vertex cone angle 175°) with nominal base diameter equal to 170 mm, and nominal recess depth equal to 2 mm. It was planned to study both influence of the recess depth and diameter on predicted bearing parameters.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was assumed similarly as in Refs. [10,16] that recess has conical shape (truncated cone, vertex cone angle 175°) with nominal base diameter equal to 170 mm, and nominal recess depth equal to 2 mm. It was planned to study both influence of the recess depth and diameter on predicted bearing parameters.…”
Section: Methodsmentioning
confidence: 99%
“…In fact, there are papers dealing with phenomena corresponding to pocket influence, but extremely rare it is included in thermoelastohydrodynamic (TEHD) models of large bearings. The only works known to the authors, which take into account this effect are papers of Pajączkowski et al [10,16], and Heinrichson [17]. Both authors include hydrostatic bearing depression of pad sliding surface in theoretical investigations of large thrust bearing properties under hydrodynamic mode of operation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study of the literature showed, that it is a common practice to not include presence of the hydrostatic recess in evaluation of hydrodynamic bearing properties. The only works known to the authors, which take into account this effect are papers of Pajączkowski [3,9] and Heinrichson [10]. Both authors include hydrostatic bearing depression of pad sliding surface in theoretical investigations of large thrust bearing properties under hydrodynamic mode of operation.…”
Section: Introductionmentioning
confidence: 99%
“…Both authors include hydrostatic bearing depression of pad sliding surface in theoretical investigations of large thrust bearing properties under hydrodynamic mode of operation. In works [3,9], Kopswerk II (Austria) power plant hydrogenerator thrust bearing (outer diameter 2.3 m) was analyzed under transient states. Relatively good agreement of calculated and measured temperatures in the pad was obtained, but this was only parameter measured and compared.…”
Section: Introductionmentioning
confidence: 99%